2015
DOI: 10.1002/ddr.21246
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of the Multidentate Hydroxypyridinonate Ligand [14C]‐3,4,3‐LI(1,2‐HOPO), a Potent Actinide Decorporation Agent

Abstract: The pharmacokinetics and biodistribution of the (14) C-labeled actinide decorporation agent 3,4,3-LI(1,2-HOPO) were investigated in young adult Swiss Webster mice and Sprague Dawley rats, after intravenous, intraperitoneal, and oral dose administration. In all routes investigated, the radiolabeled compound was rapidly distributed to various tissues and organs of the body. In mice, the 24 h fecal elimination profiles suggested that the biliary route is the predominant route of elimination. In contrast, lower fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…While the 238 Pu complexes formed with 3,4,3-LI(1,2-HOPO) or DTPA undergo relatively fast clearance and are fully expelled from the body within 24 hours [15], it has been suggested that the sustained excretion enhancement profiles in treated animals are due to intracellular uptake of the ligands and delayed clearance [25]. The pharmacokinetics and biodistribution profile of the 14 C-labeled 3,4,3-LI(1,2-HOPO) were recently characterized in the young Swiss-Webster mouse model used here [26]. After parenteral injection, the radiolabeled compound was rapidly distributed into high vascular tissues, and highest kidney and liver concentrations were seen as early as 1-hour post-administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the 238 Pu complexes formed with 3,4,3-LI(1,2-HOPO) or DTPA undergo relatively fast clearance and are fully expelled from the body within 24 hours [15], it has been suggested that the sustained excretion enhancement profiles in treated animals are due to intracellular uptake of the ligands and delayed clearance [25]. The pharmacokinetics and biodistribution profile of the 14 C-labeled 3,4,3-LI(1,2-HOPO) were recently characterized in the young Swiss-Webster mouse model used here [26]. After parenteral injection, the radiolabeled compound was rapidly distributed into high vascular tissues, and highest kidney and liver concentrations were seen as early as 1-hour post-administration.…”
Section: Discussionmentioning
confidence: 99%
“…Those differences have been discussed previously and are presumably based on respective ligand and actinide-complex physico-chemical parameters such as solubility, lipophilicity, and ionization constants [15, 20, 21]. In addition, the biliary pathway is the main mode of elimination for 3,4,3-LI(1,2-HOPO) in mice, as demonstrated by high accumulation of 14 C-labeled 3,4,3-LI(1,2-HOPO) in the feces after either parenteral or oral administration [26]. It is therefore likely that the radionuclide excretion path is ligand-driven.…”
Section: Discussionmentioning
confidence: 99%
“…The areas of study have expanded in recent years with applications in the fields of nuclear toxicology [3][4][5][6], cancer therapy (e.g., the radioisotope 225 Ac of actinium is an alpha emitter useful for targeted radiotherapy [7]), analytical chemistry [8], and in basic research in structural chemistry and reaction mechanisms [9]. All these applications have in common the need to develop pre-organised chelating agents.…”
Section: Introductionmentioning
confidence: 99%
“…is a wider spectrum actinide decorporation agent and can chelate with plutonium (Pu), americium (Am), curium(Cm), uranium (U) or neptunium (Np) ions to form stable complexes at physiological pH [12][13][14][15][16][17][18] . This novel decorporation agent is currently undergoing pre-clinical development [18] .…”
Section: Decorporation Agent: 343-li(12-hopo)mentioning
confidence: 99%
“…is a wider spectrum actinide decorporation agent and can chelate with plutonium (Pu), americium (Am), curium(Cm), uranium (U) or neptunium (Np) ions to form stable complexes at physiological pH [12][13][14][15][16][17][18] . This novel decorporation agent is currently undergoing pre-clinical development [18] . Moreover, this promising compound has higher potency and can chelate more internally deposited radionuclides than the commonly used actinide decorporation agent DTPA [14][15][16]18] .…”
Section: Decorporation Agent: 343-li(12-hopo)mentioning
confidence: 99%